The Atg8 Family of Proteins—Modulating Shape and Functionality of Autophagic Membranes - Abdollahzadeh, Iman; Schwarten, Melanie; Gensch, Thomas; Willbold, Dieter; Weiergräber, Oliver H. (Frontiers in Genetics, 2017)
Aging is a multifactorial process involving an accumulation of alterations on various organizational levels, which finally compromises viability and limits the lifespan of organisms. It is now well-established that many aspects of aging can be positively affected by (macro)autophagy, a mechanism of self-digestion found in virtually all eukaryotic cells. A comprehensive understanding of autophagy is thus expected to not only deepen our insight into the mechanisms of aging but to also open up new avenues towards increasing the healthy lifespan in humans. In this review, we focus on the Atg8 family of ubiquitin-like proteins, which play a crucial role in the autophagy process by virtue of their unique mode of reversible membrane association.